CAR-T cells containing CD28 versus 4-1BB co-stimulatory domains show distinct metabolic profiles in patients - Molly S. Cook; Ellen King; Katie R. Flaherty; Khadiza Siddika; Sophie Papa; Reuben Benjamin; Anna Schurich (Cell Reports)
Summary: Chimeric antigen receptor (CAR)-T cell therapy has led to unprecedented success in treating relapsed/refractory diffuse large B cell lymphoma (DLBCL). The most common CAR-T cell products currently in the clinic for DLBCL differ in their co-stimulation moiety, containing either CD28 or 4-1BB, which initiate distinct signaling pathways. Previous work has highlighted the importance of T cell metabolism in fueling anti-cancer function. We have studied the metabolic characteristics induced by CD28 versus 4-1BB co-stimulation in patient CAR-T cells ex vivo. Our data show that in patients, CD28 and 4-1BB drive significantly divergent metabolic profiles. CD28 signaling endows T cells with preferentially glycolytic metabolism supporting an effector phenotype and increased expansion capacity, while 4-1BB co-stimulation preserves mitochondrial fitness and results in memory-like differentiation. Despite the differences in metabolic programming, T cells in patients responding successfully to therapy were metabolically similar, irrespective of co-stimulator. In contrast, in non-responders, CD28- and 4-1BB-co-stimulated CAR-T cells were metabolically distinct from each other.